IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN DESCRIPTIVE TEXT THROUGH QUANTUM LEARNING - Meni Sihite; Johan Sinulingga (TRANSFORM : Journal of English Language Teaching and Learning, 2013)
AbstractThis study deals with the improvement of the students’ achievement in writing descriptive text through quantum learning. This study was conducted by using action research at second year of SMP N 1 Kabanjahe. The sample of this study was just one class namely: VIII-2. The number of this class was 36 students. The research was conducted in two cycles. Cycle 1 consisted of three meetings and cycle 2 consisted of two meetings. There were two kinds of data collected during the study, qualitative and quantitative data. The instrument for collecting the quantitative data was writing test while the quantitative data were gathered through interview, diary notes and observation sheet. Based on the writing test result, the students score kept improving in every test. In pre test, the mean score was 52, 61. In the test of cycle I, the mean score was 63 and the mean score in test of cycle II was 80. The conclusion is that quantum learning can improve the students’ descriptive writing achievement.Key words: Students’ Achievement, Writing, Descriptive text, Quantum Learning